Age‐based preferences for risk communication in the fentanyl era: 'A lot of people keep seeing other people die and that's not enough for them'. (26th November 2020) - Gunn, Christine M.; Maschke, Ariel; Harris, Miriam; Schoenberger, Samantha F.; Sampath, Spoorthi; Walley, Alexander Y.; Bagley, Sarah M.
Abstract: Aims: To explore how people who use fentanyl and health‐care providers engaged in and responded to overdose risk communication interactions, and how these engagements and responses might vary by age. Design: A single‐site qualitative in‐depth interview study. Setting: Boston, MA, United States. Participants: The sample included 21 people (10 women, 11 men) who were either 18–25 or 35+, English‐speaking, and reported illicit fentanyl use in the last year and 10 health‐care providers who worked directly with people who use fentanyl (PWUF) in clinical and community settings. Measurements: Open‐ended, flexible interview questions guided by a risk communication framework were used in all interviews. Codes used for thematic analysis included deductive codes related to the risk communication framework and inductive, emergent codes from interview content. Findings: We identified potential age‐based differences in perceptions of fentanyl overdose, including that younger participants appeared to display more perceptions of an immunity to fentanyl's lethality, while older people seemed to express a stronger aversion to fentanyl due to its heightened risk of fatal overdose, shorter effects and potential for long‐term health consequences. Providers perceived greater challenges relaying risk information to young PWUF and believed them to be less open to risk communication. Compassionate harm reduction communication was preferred by all participants and perceived to be delivered most effectively by community health workers and peers. PWUF and providers identified structural barriers that limited compassionate harm reduction, including misalignment of available treatment with preferred options and clinical structures that impeded the delivery of risk communication messages. Conclusions: Among people who engage in illicit fentanyl use, fentanyl‐related risk communication experiences and preferences may vary by age, but some foundational elements including compassionate, trust‐building approaches seem to be preferred across the age spectrum. Structural barriers in the clinical setting such as provider‐prescribing power and infrequent encounters may impede the providers' ability to provide compassionate harm reduction communication.